Analisis Efek Rumah Kaca serta Teknologi Penanggulangan Efek Rumah Kaca yang Terbarukan - Lajuardi, Arini Maulidiya; ., Yushardi; ., Sudarti (CV. ITTC INDONESIA, 2023)
Global warming is an increase in global temperature at the Earth's surface (within several thousand kilometers) compared to the normal/average value recorded over a standard period (World Meteorological Organization/WMO measurements: at least 30 years). Global warming is one of the impacts caused by the greenhouse effect. The greenhouse effect is a condition where the surface temperature of a celestial body, such as a planet or star, increases rapidly. This increase in temperature is caused by changes in the composition and conditions of the atmosphere around the object. The greenhouse effect can be caused by human activities and can occur naturally due to natural events such as forest burning due to a prolonged dry season. Basically, the greenhouse effect is very difficult to overcome, but we can reduce the greenhouse effect by using environmentally friendly energy such as renewable energy. With the rapid development of technology in this modern era, there are many renewable technologies that can be developed and utilized. This analysis aims to determine the process, causes and consequences of the greenhouse effect as well as the development and use of renewable energy technology to overcome the greenhouse effect.